Briefed on the development and progress of CCUS projects in China, USA, Western Europe, Russia, Norway, India, and Indonesia: a journal review - Rudianto Rimbono; Raldi H. Koestoer (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The global commitment to manage climate change issues is getting stronger and stronger. Therefore this review is carried out with the objective to obtain recent progress of efforts on emission control and handling through CCUS by various countries around the world. This review is carried out to highlight the development of carbon capture utilization and/or storage (CCUS) in China, the USA, and India, as these countries are known to be the most energy consumption countries. Its campaign to reduce emissions will contribute significantly to the effort of managing the global warming issue. The method used in this study is a literature review on the policies, studies, and projects mainly in China, and several other countries for comparison. The review found that although China is relatively late in doing such activities on climate change, but the progress is significantly faster than the others. The numbers of studies and patents are much higher than other countries, and the central and local governments issued a number of policies to help encourages the industries. The USA is known as one of the leading countries implementing CCS/CCUS and still creating incentive policies. European, Russian, and Indian countries pay serious attention to this effort and implement it while Indonesia as a non-industrial country is catching up.. From this literature research, it can be concluded that the technology for implementing CCUS is still at a high cost so policy and government funding support is needed as well as non-traditional sources of capital source such as green funding, carbon trading, etc.